Financial Performance Analysis Village Fund Management Based On Effectiveness Ratio And Growth Ratio In Negeri Hitu Lama Central Maluku Regency - Christianity, Restia; Faisal, Muhammad (SEAN Institute, 2024)
Good village financial management will affect the progress of a village. Village financial management not only requires reliable human resources but must also be supported by adequate finances. Village financial management has a very large influence on the fate of a village because whether it is able to develop or not depends on how its finances are managed. Good village financial management will also show good village government performance. This study aims to determine how good the financial performance of village fund allocation management is based on the effectiveness ratio and growth ratio in Negeri Hitu Lama, Central Maluku Regency. The type of research used in this study is quantitative descriptive. The data processed is the financial report of village fund allocation in the village revenue and expenditure budget from 2019 to 2023. The data collection technique used is the document technique and literature study. The data analysis technique used in this study is quantitative descriptive with the formula: effectiveness ratio and growth ratio. The results are that on average, the management of village fund allocation is quite effective, although the ratio of income and expenditure is still relatively low.